'Ancient lore with modern appliances': networks, expertise, and the making of the Open Polar Sea, 1851–1853. Issue 3 (September 2021) - Kaalund, Nanna Katrine Lüders; Woitkowitz, John
Abstract: This article provides a transnational analysis of the campaigns for the organization of expeditions to the central Arctic region by the American explorer Elisha Kent Kane and the Prussian cartographer August Petermann between 1851 and 1853. By adopting a comparative approach, this study focuses on three interventions in the history of Arctic science and exploration: the construction of scientific expertise surrounding the relationship between the 'armchair' and the field, the role of transnational networks, and the significance of maps as travelling epistemic objects in the production of knowledge about the Arctic regions. In bringing both campaigns in conversation with each other, this article demonstrates that the histories of Kane's and Petermann's campaigns did not constitute isolated episodes but form part of a transnational nexus of imperial science and Arctic exploration in the nineteenth century. Moreover, based on research in libraries and archives in the United States, Germany and England, this study reconnects otherwise siloed collections and contributes new findings on the interpersonal networks of science and exploration. Finally, this article illustrates the importance of adopting comparative transnational approaches for understanding the fluid and reciprocal nature of Arctic science throughout the transatlantic world.